Financing the Green Transition: Exploring the Role of Financial Inclusion and Renewable Energy in Driving Green Growth into More and Less Inclusive Financial Systems in the MENA Countries - Saidi, Hichem (International Journal of Energy Economics and Policy, 2025)
This research examines the relationship among renewable energy, financial inclusion, and green growth in the MENA region, focusing on how financial access and the adoption of clean energy contribute to green growth. Using a dataset of 12 MENA countries from 2010 to 2023, and applying the System Generalized Method of Moments (SGMM), we examine the individual and interactive effects of financial inclusion and renewable energy on green growth. To account for the considerable heterogeneity within the region, we distinguish between countries with more inclusive financial system, and those with less inclusive systems, where financial access remains limited. As consequently, we used the fixed and random effect. For the full sample, the results reveal that financial inclusion significantly reduces green growth, while renewable energy does not exert any significant effect. For the disaggregate analysis, the effect of financial inclusion and renewable energy differs across countries with more inclusive financial systems, and countries with less inclusive systems. Moreover, the effectiveness of these drivers is strongly influenced by institutional quality and domestic investment. For the combined effect, we found that the interaction between financial inclusion and renewable energy promotes green growth only in countries with more inclusive financial systems, while it reduces green growth in countries with less inclusive systems. The study provides novel, region-specific evidence and offers practical guidance for policymakers to design strategies that align financial inclusion and renewable energy initiatives with long-term sustainability goals in the MENA region.